Washback of the Vienam six-levels of foreign language proficiency framework on institutional policies and teaching English for non-English major students at national university of arts education - Đinh, Thi Phuong Hoa (Đại học quốc gia Hà Nội, 2020)
In educational research, tests have been considered one of the dominant determiners of what happens in classrooms that can influence teaching and learning activities - English proficiency tests in particular. In this paper, the influences have been classified directly and indirectly, either positively or negatively, or both. Therefore, the positive or negative influences of tests are related to washback. This study investigated how The Vietnam Six-levels of Foreign Language Proficiency Framework and its English proficiency tests affect institutional policies and teaching of English as foreign language for non-English major students at National University of Arts Education in Hanoi, Vietnam.